Exhaust gas circulation on a diesel engine fisheries vessel to improve performance using with biodisel B40 - Hendra Purnomo; Barokah Barokah; Kriswaanto Kriswaanto; Iksan Saefudin; Putu Deny Darmawan; Harlian Harlian (Politeknik Kelautan dan Perikanan Dumai, 2026)
Along with advancements in mechanical engineering technology for fishing vessel, particularly in diesel engines, numerous developments have been made to achieve maximum performance. This study aims to determine the effect of applying an exhaust gas recirculation (EGR) system on the performance of diesel engines using B40 biodiesel fuel. The use of biodiesel as an alternative fuel is growing because it can reduce dependence on fossil fuels and reduce exhaust emissions. However, the use of high-blend biodiesel such as B40 can affect combustion characteristics and engine performance. Therefore, a method is needed to optimize engine performance, one of which is through the application of an EGR system. The research method was conducted experimentally by testing diesel engines using B40 biodiesel fuel. The testing was carried out directly by operating diesel engines equipped with EGR systems. The parameters observed included engine performance, such as power and specific fuel consumption. Data was collected under varying load conditions. The data obtained was then analyzed to determine the effect of EGR on engine performance improvement. The results indicate that the application of an exhaust gas recirculation system in diesel engines utilizing B40 biodiesel fuel can influence the combustion process, thereby affecting engine performance. At a valve opening of 25%, the best SFOC can be achieved. The results showed that the application of an exhaust gas recirculation system in diesel engines using B40 biodiesel fuel can affect the combustion process, thereby impacting engine performance. Based on the test results, it can be concluded that the application of an exhaust gas recirculation (EGR) system in diesel engines fueled by B40 biodiesel improves engine efficiency.